Pengelompokan Persediaan Spare parts Menggunakan Analisis FSN di PT. XYZ - Amalia, Wahyuni; Pangestu, Adryan; Oktavia, Nurike (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Spare part inventory is very important for the continuity of forklift repair and maintenance activities at PT. XYZ. Currently it is not known which spare part inventory groups are in higher demand (fast moving) compared to other spare parts. This can have an impact on determining inaccurate inventory amounts. This research aims to determine which spare part groups are fast moving, slow moving and non-moving based on turnover ratio. From the results of calculations for 45 types of spare parts, there are 23 types of goods that are fast moving, 14 types of goods are slow moving and 6 types of goods are non-moving, while the other 2 do not have an inventory turnover ratio. Based on these groupings, the Company can determine the optimal order quantity to avoid stock shortages for fast moving goods.